Promoting prevention: Evaluating a multi-agency initiative to prevent youth offending in Swansea. - Stephen Case (2004)
This thesis presents the research and evaluation of ‘Promoting Prevention’, a multiagency, multiple intervention initiative to prevent youth offending in Swansea that is predicated on the generation of systematic information through official and self- reported sources. The thesis discusses how structures and processes within Promoting Prevention have developed through a rolling dynamic between information generation and system reproduction, with particular emphasis upon consultation with young people and key stakeholders.An individual study computer questionnaire, underpinned by the risk factor prevention paradigm, assessed young people’s self-reported attitudes, perceptions and behaviour in order to associate them with a range of risk and protective factors for offending. Statistical analysis identified that exposure to multiple risk factors in the key domains of the young person’s life (i.e. family, school, neighbourhood, lifestyle, personal/individual) was significantly linked to ever and active offending, particularly for males. Several key factors within each domain were highlighted as predictive of ever and active offending. When placed in the context of official and self-reported statistics locally, nationally and internationally, there was a clear overlap in salient issues for young people and identified risk factors, although levels of self-reported drug use and offending were generally higher in Swansea.Systems analyses adapted the grounded theory methodology and utilised interviews with key stakeholders to produce narrative reports and maps of Promoting Prevention components (organisations, committees, documents, individuals) to elucidate the complex, cross-cutting and reflexive nature of the initiative.Overall levels of (self-reported and official) permanent school exclusion and (self- reported and official) ever and active offending in Swansea have fallen since the inception of Promoting Prevention. This indicates that Promoting Prevention can tentatively claim to be successfully addressing offending behaviour by targeting interventions based on risk factors identified by young people. There is a commitment amongst key stakeholders to Promoting Prevention principles and strategies such as consultation and developing a reflexive relationship between research, information and practice. This highlights Promoting Prevention as a modem example of an holistic, rights-based crime prevention initiative underpinned by an ethos of consultation and responding to information relevant to the local context.